HOW DO THE SOCIO-ECONOMIC INDICATORS INFLUENCE THE TRAVEL BEHAVIOUR PATTERN? CASE STUDY AMMAN-JORDAN - Shbeeb, Lina (Journal of Applied Engineering Science, 2022)
Limited research has been conducted in developing countries on travel behavior and its prediction. This study aimed to investigate if socio-economic conditions affect travel behavior patterns in Amman, Jordan, and propose regression models for trips defining the contributory factors. A total of 681 interviews were conducted with households (210) and workplace employees (335), assessing behavioural travel styles in two neighbourhoods with different characteristics. Compared to residents of high-income areas (HIA), residents of low-income areas (LIAs) travel more by all modes of transportation; in LIA and HIA, the trip rate per person was (2.2) and (2.0), respectively, while in low-income and high-income areas, the number of trips per household was 5.14 (153.6 minutes) and 3.7 (155 minutes). Most household trips in low-income neighbourhoods, mainly for education and work, were made on foot, while private cars were more common in high-income areas. For trips related to the office and shops, the private car was the most common mode of transportation. In low-income neighbourhoods, shared taxis were commonly used for household and shop trips, and buses were often used for commutes. School and university students, as well as household size, provided valid trip predictions. Employees can predict work trips to the office, customer visits, and shop-related trips.
Keywords: travel, behaviour pattern, income level, regression analysis